2010
DOI: 10.1007/s00299-010-0825-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and vegetative cutting capacity are under distinct genetic control in Coffea canephora Pierre

Abstract: The purpose of the study was to evaluate the possible genetic effect on vegetative propagation of Coffea canephora. Diversity for somatic embryogenesis (SE) ability was observed not only among two groups of C. canephora Pierre (Congolese and Guinean), but also within these different genetic groups. The results therefore showed that, under given experimental conditions, SE ability is depending on genotype. Furthermore the detection of quantitative trait loci (QTLs) controlling the SE and cutting abilities of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 50 publications
0
6
0
4
Order By: Relevance
“…Genotype dependence for induction of SE from explants of woody perennials has been demonstrated in a number of other studies including angiosperms, such as Quercus robur (San-José et al 2010), sweetgum (Merkle and Battle 2000), and CoVea canephora (Priyono et al 2010). In the latter species, the authors compared a Congolese and Guinean group of plants and identiWed six quantitative trait loci (QTL) that were responsible for diVerential SE ability in leaf explant cultures.…”
Section: Sample Copy Numbermentioning
confidence: 93%
“…Genotype dependence for induction of SE from explants of woody perennials has been demonstrated in a number of other studies including angiosperms, such as Quercus robur (San-José et al 2010), sweetgum (Merkle and Battle 2000), and CoVea canephora (Priyono et al 2010). In the latter species, the authors compared a Congolese and Guinean group of plants and identiWed six quantitative trait loci (QTL) that were responsible for diVerential SE ability in leaf explant cultures.…”
Section: Sample Copy Numbermentioning
confidence: 93%
“…Some studies indicated that the somatic embryogenesis is determined mainly by the genotype and physiological stage of the explant (Molina et al 2002, Wilhelm et al 2005, Li et al 2014, Henao et al 2018. In some cases, induction is higher when young zygotic embryos are used, but in other species, the maximum efficiency of SE is reached in the most advanced stage of development (Gaj 2004, Priyono et al 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Dentro de los factores limitantes para la transformación estable, figura el genotipo, que va a determinar en gran medida el éxito en la regeneración a partir de las células transformadas. En diferentes especies se han encontrado varios QTLs (Quantitative Traits Loci) que contienen genes relacionados con la regeneración, lo que indica que son varios genes los que influyen en este proceso y explica las diferencias encontradas en cuanto a la capacidad regenerativa en distintos cultivares de la misma especie (Priyono et al 2010, Zhenzhen et al 2015. En el caso de la vid, las variedades 'Chardonnay' y 'Thompson Seedless' han sido las más utilizadas como ocurre en otros cultivos donde se utilizan comúnmente aquellas con mejor aptitud para la regeneración.…”
Section: Resultsunclassified
“…Interspecific and intraspecific variability for regeneration ability were commonly found. Different QTLs have been related to regeneration in different species (PRIYONO et al 2010, ZHENZHEN et al 2015, which manifests the implication of several genes in the regeneration process. On the other hand, each genotype manifests a specific sensitivity to the Agrobacterium strain, as well as to the selective agents added to the medium to impede regeneration from non-transgenic cells and to the antibiotics applied to eliminate Agrobacterium after transformation (ZHOU et al 2014).…”
Section: Discussionmentioning
confidence: 99%